The Impact of Environmental Factors on Image Qualities of Holographic Projection - Shihchien Chan (Journal of Applied Science and Engineering, 2025)
This study primarily investigates the variations in image quality resulting from environmental factors in holographic projection, with the external environment being considered as a variable. The overall research employs a combination of experimental methods. The single-sided holographic projection experimental test chamber is set up to simulate experimental conditions. Simulation tests are conducted to evaluate the impact on images, capturing images of the reflective screen for three predefined environmental variables: background light intensity, background light color and background color. OpenCV image analysis software is employed to quantitatively analyze the image quality. The content of image quality analysis focuses on the average color of R/G/B, contrast, sharpness, and saturation. The study reveals that there is minimal contrast difference between white light and yellow light sources; however, under low illumination, white light outperforms yellow light in sharpness, while yellow light exhibits superior saturation. In high ambient light conditions, both white light and yellow light show a decreasing trend in contrast. When background color changes, image quality is generally better on a black background compared to gray and white backgrounds. This research provides a profound understanding of the impact of external environmental factors on holographic projection, contributing insights into the changes in image quality and the quality control of future holographic projection settings.